Obestatin modulates ghrelin's effects on the basal and stimulated testosterone secretion by the testis of rat: an in vitro study - Afsar, T; Jahan, S; Razak, S; Almajwal, A; Abulmeaty, M; Wazir, H; Majeed, A (Physiological research, 2017)
The functional antagonism between obestatin and ghrelin in the testis is under investigation. We investigated the ability of obestatin to counteract the inhibitory effect of ghrelin on basal and stimulated testosterone (T) secretion in vitro. Testicular strips from adult rats were incubated with 10 ng/ml and 100 ng/ml of obestatin alone, ghrelin alone and obestatin + ghrelin. Obestatin modulation of stimulated T secretion was evaluated by incubation of testicular samples with 10 ng/ml and 100 ng/ml obestatin, ghrelin and obestatin + ghrelin in the absence and presence of 10 IU of human chorionic gonadotrophin (hCG). T concentrations in the hCG treated groups were significantly (P<0.0001) higher than those in the control groups. Obestatin caused a significant increase in basal T secretion in a dose-dependent manner; however, obestatin at the both 10 ng/ml and 100 ng/ml significantly (P<0.0001) increased hCG-stimulated T secretion. In contrast, ghrelin in a dose-dependent manner significantly (P<0.001) decreased both basal and hCG-induced T secretion by testicular slices. Obestatin opposed the inhibitory effect of ghrelin on T secretion under both basal and hCG-stimulated conditions at all doses tested. In conclusions, administration of obestatin was able to antagonize the inhibitory effect of ghrelin on testosterone secretion in vitro.
Keywords: krysa rodu Rattus; mužské pohlaví; Male; synergismus léků; ghrelin; vztah mezi dávkou a účinkem léčiva; peptidové hormony; Rats; Ghrelin; Peptide Hormones; Animals; Dose-Response Relationship, Drug; testosteron; testis; zvířata; Drug Synergism; Testis; Testosterone; Rats, Sprague-Dawley; potkani Sprague-Dawley